Essential amino acid-enriched whey enhances post-exercise whole-body protein balance during energy deficit more than iso-nitrogenous whey or a mixed-macronutrient meal: a randomized, crossover study. Issue 1 (7th January 2021) - Gwin, Jess A.; Church, David D.; Hatch-McChesney, Adrienne; Allen, Jillian T.; Wilson, Marques A.; Varanoske, Alyssa N.; Carrigan, Christopher T.; Murphy, Nancy E.; Margolis, Lee M.; Carbone, John W.; Wolfe, Robert R.; Ferrando, Arny A.; et al.
Abstract: Background: The effects of ingesting varying essential amino acid (EAA)/protein-containing food formats on protein kinetics during energy deficit are undetermined. Therefore, recommendations for EAA/protein food formats necessary to optimize both whole-body protein balance and muscle protein synthesis (MPS) during energy deficit are unknown. We measured protein kinetics after consuming iso-nitrogenous amounts of free-form essential amino acid-enriched whey (EAA + W; 34.7 g protein, 24 g EAA sourced from whey and free-form EAA), whey (WHEY; 34.7 g protein, 18.7 g EAA), or a mixed-macronutrient meal (MEAL; 34.7 g protein, 11.4 g EAA) after exercise during short-term energy deficit. Methods: Ten adults (mean ± SD; 21 ± 4 y; 25.7 ± 1.7 kg/m 2 ) completed a randomized, double-blind crossover study consisting of three, 5 d energy-deficit periods (− 30 ± 3% of total energy requirements), separated by 14 d. Whole-body protein synthesis (PS), breakdown (PB), and net balance (NET) were determined at rest and in response to combination exercise consisting of load carriage treadmill walking, deadlifts, and box step-ups at the end of each energy deficit using L-[ 2 H5 ]-phenylalanine and L-[ 2 H2 ]-tyrosine infusions. Treatments were ingested immediately post-exercise. Mixed-muscle protein synthesis (mixed-MPS) was measured during exercise through recovery. Results: Change (Δ postabsorptive + exercise to postprandial + recovery [mean treatment difference (95%CI)]) in whole-body (g/180 min) PS was 15.8 (9.8, 21.9; P = 0.001) and 19.4 (14.8, 24.0; P = 0.001) greater for EAA + W than WHEY and MEAL, respectively, with no difference between WHEY and MEAL. ΔPB was − 6.3 (− 11.5, − 1.18; P = 0.02) greater for EAA + W than WHEY and − 7.7 (− 11.9, − 3.6; P = 0.002) greater for MEAL than WHEY, with no difference between EAA + W and MEAL. ΔNET was 22.1 (20.5, 23.8; P = 0.001) and 18.0 (16.5, 19.5; P = 0.00) greater for EAA + W than WHEY and MEAL, respectively, while ΔNET was 4.2 (2.7, 5.6; P = 0.001) greater for MEAL than WHEY. Mixed-MPS did not differ between treatments. Conclusions: While mixed-MPS was similar across treatments, combining free-form EAA with whey promotes greater whole-body net protein balance during energy deficit compared to iso-nitrogenous amounts of whey or a mixed-macronutrient meal. Trial registration: ClinicalTrials.gov, Identifier no. NCT04004715 . Retrospectively registered 28 June 2019, first enrollment 6 June 2019